Examining the relationship between visual and sensorimotor skills and in-game performance in men`s Division II college basketball players - Takacs, M.; Snyder, B.; Finn, B.; Davis, S. (International Journal of Exercise Science Conference Proceedings, 2025)
Athletic performance in basketball is strongly influenced by sensorimotor skills such as reaction time, visual tracking, and perceptual-cognitive processing. Previous research has shown that skilled players outperform less-skilled counterparts in central and peripheral processing tasks, which are critical for tracking teammates, opponents, and the ball during dynamic play. There is very limited research on visual and sensorimotor skills at the NCAA Division II level, highlighting the need for further investigation. PURPOSE: To examine the relationship between preseason visual and sensorimotor skills and in-game performance statistics in NCAA Division II men`s basketball players. METHODS: Ten NCAA Division II men`s basketball players (20.5 ± 1.43 years; 1.95 ± 0.09 m; 94.54 ± 9.47 kg) completed preseason testing on the Senaptec Sensory Station, which assesses 10 visual and sensorimotor skills. Official game statistics were collected via official box scores from the 2024-2025 season, including points, assists, rebounds, steals, blocks, and shooting efficiency: field goal (FG%), free throw (FT%), and 3-point (3PT%) percentages. Pearson correlation analyses and level of significance were performed to examine associations between sensorimotor skills and performance metrics. RESULTS: Significant positive correlations were found between binocular visual clarity and FG% (r = 0.636, p = 0.048). A trend toward significance was found between near-far quickness and blocks (r = 0.627, p = 0.052). CONCLUSION: These findings suggest that select sensorimotor skills were associated with offensive and defensive in-game basketball performance. Specifically, greater binocular visual clarity appeared to be associated with higher FG%. Additionally, near-far quickness demonstrated a trend toward association with shot-blocking, suggesting a possible connection to defensive skill that warrants further examination. SIGNIFICANCE/NOVELTY: This study is among the first to directly examine the relationship between preseason sensorimotor skills and in-game statistics in NCAA Division II men`s basketball players. These results suggest that sensorimotor training may help identify player strengths and weaknesses, with potential for targeted visual drills to enhance performance. Incorporating this type of training into preseason programs may provide players and coaches with valuable insights and warrants further investigation.